Phenotypic and Production System Characterization of Sudanese Watish Desert Sheep in Sinnar State, Sudan - Mohamed, Sara E. Ibrahim; Omer, Romaz M. A.; Musa, L. M. A.; Jawasreh, Khaleel I. Z.; Ahmed, Mohammed-Khair A. (Journal of Veterinary Medicine and Animal Production, 2021)
This research was conducted to contribute to establishing base line data for the phenotypic characterization of Watish sheep and their production system for future conservation and improvements efforts. A semi-structured questionnaire, field observations and linear body measurements were used to gather information from 59 Watish sheep owners in 7 villages. Body measurements were collected on 156 individuals and the data were classified according to sex and age. Gathered data were summarized and analyzed mainly in the form of descriptive statistics. Watish sheep were found to be produced under a nomadic system (81.4%), a sedentary system (8.5%) or a semi nomadic system (10.2%). Supplementary feeding was adopted by 67.2% of owners and of those, 26.3% fed concentrates supplements. Most owners (81.0%) raised breeding rams from own flock while 17.3% borrowed rams from neighbouring flocks. The main production constraints were water (25.0%), feed (20.6%), disease (19.6%), capital (18.1%), and security (16.7%). The highest mortality rate among all classes of animals, particularly, new born lambs and nursing ewes occurred in dry summer. The overall mean of body length, heart girth, barrel circumference, height at withers and tail length were 63.87±0.48, 81.25±0.66, 93.61±0.87, 76.51±0.42 and 62.37±0.6, respectively. All correlations were positive and significant between different morphometric measurements. No association were observed between the sharing of management by family members (χ2 = 3.333), breeding system(χ2=1.262), concentrate provision(χ2=5.276), vaccination (χ2=1.280) and record keeping (χ2 = 0.811) and education level of owners. However, there was a significant association between purpose of rearing sheep (χ2=17.524) and disease occurrence (χ2=11.058) and level of education of owners. A highly significant association was observed between identification method and education level (χ2=18.133). This study highlights the need for greater control of environmental factors in order to improve Watish sheep production.